Theoretical Study of Metal Ion Impact on Geometry and Bond Vibrational Properties of Salophen Compound - Manurung, Tety Wahyuningsih; Afthoni, Muhammad Hilmi; Steven , Kur Yehezkiel; Pasaribu, Marvin Horale; Ariefin, Mokhamat; Alfanaar, Rokiy (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2024)
Coordination compounds are compounds consisting of a metal atom as a center surrounded by ligands, which are important in applications such as catalysts and pharmacological sensors. Salophen, as one of the organic ligands, is capable of forming complexes with various metal ions. This study uses a computational chemistry approach to model the geometry, electronic properties, and bond vibrations of compound complexes between salophen and Zn(II), Cd(II), and Hg(II) metal ions using the PM6 semiempirical method. Modeling results show that the metal ion radius affects the dihedral angle of salophen, with the largest angle occurring in the complex with Hg(II) ions, while the complex with Cd(II) ions tends to be close to planar. FTIR analysis shows that the vibrational pattern is influenced by the bond length of salophen with metal ions. In addition, the HOMO-LUMO gap energy of the three complexes is also slightly different, with the Zn-salophen complex having the smallest Egap of 0.25709 eV.